Map - St. Mary's River - Cornfield Harbor and Pt. Lookout Maryland (1861) - Survey of the Coast of the United States (1861)
Nautical chart of the coastal areas around Pt. Lookout, MD. Includes Chesapeake Bay, Potomac River, and St. Mary's River. Water depths and some land features. Includes tide tables, sailing directions, and lighthouse locations.